Mycelial biomass and biochemical properties of proteases produced by Lentinus citrinus DPUA 1535 (Higher Basidiomycetes) in submerged cultivation - Kirsch, Larissa de Souza; Ebinuma, Valéria de Carvalho Santos [UNESP]; Teixeira, Maria Francisca Simas (Begell House Inc, 2013)
The cultivation of Lentinus citrinus for mycelial biomass and protease production under different carbon and nitrogen sources was studied in submerged cultivation. The nutritional source concentration for protease production was evaluated using a full factorial design. For mycelial biomass maltose (4.94 mg/mL) and beef extract (5.45 mg/mL), carbon and nitrogen sources presented the best results, respectively. The maximum protease activity was 73.33 U/mL with fructose (30.0 g/L) and beef extract (10.0 g/L). Proteases showed maximum activity at 40°C and pH 7.0, which exhibited high stability at experimental conditions. The final part of this work was devoted to estimating the main thermodynamic parameters of the irreversible enzyme inactivation (ΔH* = 17.86 kJ/mol, ΔG* =102.09 kJ/mol, ΔS* = -260.76 J/mol×K) through residual activity tests carried out at 25-70°C, by making use of Arrhenius and Eyring plots. © 2013 Begell House, Inc.
Keywords: Lentinus citrinus; Medicinal mushrooms; Mycelial biomass; Nitrogen and carbon sources; Protease activity